2022
DOI: 10.3390/nu14142914
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometrics, Hemoglobin Status and Dietary Micronutrient Intake among Tanzanian and Mozambican Pigeon Pea Farmers

Abstract: Inadequate consumption of micronutrient-dense and protein-rich foods such as vegetables, legumes and meat is an important contributing cause for anemia and deficiencies of vitamin A and iron in rural communities of Tanzania and Mozambique. A cross-sectional study was conducted to assess the nutritional status (anthropometrics and hemoglobin) and diets in particular micronutrient intake of female and male pigeon pea farmers from Lindi, Tanzania, and Gurué, the Zambézia province of Mozambique. A total of 1526 fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Furthermore, even a little quantity of traditionally consumed, locally grown vegetables could boost micronutrient intake, enhance general health and nutritional status. Additionally, it has been demonstrated that greater crop diversification can improve our diets by raising calorie and nutrient consumption [6,7,9,12,27]. These results highlight the significance of encouraging crop diversity and vegetable-based agricultural methods to enhance the nutritional status and health of vulnerable communities.…”
Section: The Role Of Food Based Intervention In Improving Micronutrie...mentioning
confidence: 97%
See 3 more Smart Citations
“…Furthermore, even a little quantity of traditionally consumed, locally grown vegetables could boost micronutrient intake, enhance general health and nutritional status. Additionally, it has been demonstrated that greater crop diversification can improve our diets by raising calorie and nutrient consumption [6,7,9,12,27]. These results highlight the significance of encouraging crop diversity and vegetable-based agricultural methods to enhance the nutritional status and health of vulnerable communities.…”
Section: The Role Of Food Based Intervention In Improving Micronutrie...mentioning
confidence: 97%
“…In Tanzania and Ghana, younger children's mean hemoglobin levels and anemia were found to be significantly affected by improved home gardening programs [9,12,19]. In Ethiopia, Rwanda, Ghana, and Burkina Faso, it was reported that nutrition-sensitive agricultural interventions had an effect on the variety of maternal and child diets, food intake, micronutrient status, and weight-specific nutritional status markers [2,8,19,22,25,29].…”
Section: The Role Of Food Based Intervention In Improving Micronutrie...mentioning
confidence: 99%
See 2 more Smart Citations